Колаборативен здравствен информационен систем базиран на нови технологии - Гаврилов, Гоце (ФИНКИ, УКИМ, Скопје, 2017)
Information technology is increasingly used in healthcare with the goal to im-prove and enhance medical services and to reduce costs. One of the areas with greatest needs having available information at the right moment and with high accuracy is healthcare. Information systems play a significant role in the improv-ing of health and healthcare, as well as in the planning and financing of health services. The use of information and communication technology (ICT) in health care is proposed as a useful tool to increase efficiency, improve access, and improve the quality of care. The main argument for introducing eHealth services is its cost-saving potential. Electronic Health Record (EHR) systems are core applications in any e-Health environment and represent basic services for healthcare information technology platforms. The widespread use of EHR, building a secure EHR sharing environ-ment has attracted a lot of attention in both healthcare industry and academic community. Collaborative health care information system, presented in this thesis, can serve as a valuable input for the healthcare authorities in making decisions related to creating health care policies. The aim of this doctoral thesis is to define the collaborative health information system based on new technology that would be possible: increasing health pre-vention, timely and faster delivery of medical data within the healthcare system, able to send various notifications to users, automatic transmission of data con-cerning between different actors, increased flexibility in the collection of medical data, using evidence-based medicine and its implementation in information sys-tems, obtaining information and data for timely planning of health measures and policies. This model will create an opportunity for increased health care, on the one hand, and increased capacity of health institutions on the other, resulting in a reduction of overall costs for patients and healthcare providers and improve the quality of life of the user. Reduced costs in turn will contribute to the timely planning of health penny for new services and research to improve health care. Better health care is provided by sending and exchange of data and information between various participants in the system.
Collaborative Health Information System based on new technologies
Докторска дисертација одбранета во 2017 година на Факултетот за информатички науки и компјутерско инженерство во Скопје, под менторство на проф. д–р Владимир Трајковиќ.
Keywords: e-services, web portal, Electronic health record (EHR), Electronic Identity (eID), information systems, and collaborative systems